Transmedia storytelling in expanding audience’s engagement: A phenomenological study of Nussa Rara - Hasan bin Jali; Mawaidi; Lalu Habiburrahman (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
The evolution of digital storytelling has transformed audience engagement, particularly through the utilization of multiple media platforms. This study aims to explore how the Nussa Rara franchise has expanded its narrative universe across various platforms—YouTube, a feature film, interactive AR, and merchandise—to enhance audience experience and engagement. Using a qualitative research approach, the study analyzed content and collected audience feedback through interviews and surveys. Results indicate that each platform uniquely contributes to deepening the narrative experience, with YouTube providing accessibility, the film adding emotional depth, AR enhancing interactivity, and merchandise creating a tangible connection to the story. These findings underscore the effectiveness of integrated media strategies in building compelling transmedia narratives.